The Effect of Timing of Grassland Management on Plant Reproduction. (4th March 2012) - Lennartsson, Tommy; Wissman, Jörgen; Bergström, Hanna-Märtha
Abstract : Seminatural grasslands are maintained by regular anthropogenic disturbance, usually grazing or mowing. Management action late in the growing season was historically more common than today. Two experimental grazing regimes, continuous stocking from May to September and late-onset grazing from mid-July, were compared in two Swedish grasslands. Effects on flowering and fruit production were studied and related to plant functional traits. Change in vegetation composition over six years was analysed in one grassland. Delayed onset of grazing enhanced fruit production up to four times. Phenology of reproduction was the most important plant trait explaining differences in reproduction among species. Diversity of vascular plant species was higher after six years of late-onset grazing. No differences in vegetation height or proportion of grazed shoots were found by the end of the season. The results suggest that early reproduction may function as an escape from damage and that late onset of grazing may be used as a substitute for labour-intense traditional mowing.